Calibration of the LOFAR antennas - Hörandel, Jörg R.; Buitink, S.; Corstanje, A.; Enriquez, J. E.; Falcke, H.; Karskens, T.; Krause, M.; Nelles, Anna; Rachen, J. P.; Rossetto, L.; Schellart, P.; Scholten, O.; et al. (Proceedings of Science, 2015)
Extensive air showers create short nanosecond-scale pulses in the radio frequencies. These pulses have been measured successfully in the past years at the Low-Frequency Array (LOFAR). Due to the short duration and emission of the signal in the atmosphere, methods based on flux calibration of known sources as used in radio astronomical observations cannot be applied to establish an absolute calibration. To overcome this, we present three approaches that were used to check and improve the antenna model of LOFAR, and to provide an absolute calibration for air shower measurements. Two include the calibration with made-made sources, while one is using the Galactic radio emission. A source has been used that allows the cross-calibration of LOPES, Tunka-Rex and LOFAR. In future work these results can be used as an absolute scale for measurements of astronomical transients with LOFAR.
CRIS-Team Scopus Importer:2023-08-15